The Geopolitics of Tourism: Mobilities, Territory, and Protest in China, Taiwan, and Hong Kong. Issue 2 (3rd March 2016) - Rowen, Ian
Abstract : This article analyzes outbound tourism from mainland China to Hong Kong and Taiwan, two territories claimed by the People's Republic of China, to unpack the geopolitics of the state and the everyday, to theorize the mutual constitution of the tourist and the nation-state, and to explore the role of tourism in new forms of protest and resistance. Based on ethnographies of tourism practices and spaces of resistance conducted between 2012 and 2015 and supported by ethnographic content analysis, this article demonstrates that tourism mobilities are entangled with shifting forms of sovereignty, territoriality, and bordering. The case of China, the world's fastest growing tourism market, is exemplary. Tourism is profoundly affecting spatial, social, political, and economic order throughout the wider region, reconfiguring leisure spaces and economies, transportation infrastructure, popular political discourse, and geopolitical imaginaries. At the same time that tourism is being used to project Chinese state authority over Taiwan and consolidate control over Tibet and Xinjiang, it has also triggered popular protest in Hong Kong (including the pro-democracy Umbrella Movement and its aftermath), and international protest over the territorially contested South China Sea. This article argues that embodied, everyday practices such as tourism cannot be divorced from state-scale geopolitics and that future research should pay closer attention to its unpredictable political instrumentalities and chaotic effects. In dialogue with both mobilities research and borders studies, it sheds light not only on the vivid particularities of the region but on the cultural politics and geopolitics of tourism in general.